The Effect Of Placement And Career Development On Employee Performance At Pt Abadi Jaya Solusindo In Tangerang City - Banjal, Teul Panda; Januar, Dedy; Susanto, Agus; Haris, Ruli; Putranto, Agung Tri (Doctoral Program of Social Science Pasundan University, 2024)
This study aims to determine the effect of placement and career development on employee performance at PT Abadi Jaya Solusindo in Tangerang City. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study placement has a significant effect on employee performance of 41.6%, the hypothesis test obtained t count> t table or (8.133> 1.986). Career development has a significant effect on employee performance of 43.8%, the hypothesis test obtained t count> t table or (8.508> 1.986). Placement and career development simultaneously have a significant effect on employee performance of 52.6%, the hypothesis test obtained F count> F table or (51.106> 2.700).